THE CHALLENGES OF POLICY IMPLEMENTATION IN AFRICA AND SUSTAINABLE DEVELOPMENT GOALS - Ajulor, Omoniyi Victor (PEOPLE: International Journal of Social Sciences, 2018)
In recent times, the continent of Africa has found itself at the crossroads caused by economic recession, criminality, corruption and ineptitude leadership that has led to national insecurity and poverty. It is the better time now to join forces in searching for solutions to address the multifaceted challenges facing sustainable development in Africa. The study, therefore, examines the challenges of policy implementation in Africa and Sustainable Development Goals (SDGs) with a particular reference to Nigeria. In doing this, a survey study was carried out, and a questionnaire administered while chi-square was used to test the hypotheses. All the data obtained were computer processed through Statistical Packages for Social Sciences (SPSS). Key informant interview was also carried out. The study discovers that Nigeria and most countries in Africa have entered economic recessions because of policy implementation challenges such as unrealistic goal setting, political patronage, neglect of target beneficiaries and lack of consideration of policy environment. The study recommends that Africa should set policy goals that are implementable. The SDGs should be reviewed by African countries to domesticate the goals with environmental considerations properly. Africa should do more to check corruption. Policies designed for implementation by the Federal government in Nigeria should include the state and local government contents. There should be the participation of the target beneficiaries in any policy design to better their lives. These will ensure ownership and avoid sabotage. With these, SDGs will make the significant impact in Africa.